Isu-Isu Kosakata Matematis dalam Pembelajaran Matematika - Sugiatno, Sugiatno; Husna, Nurul (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to examine the problem of mathematical vocabulary as the main issues of mathematics education. Through library research with literature review and interviews with several mathematics teachers, data obtained are relevant to the purpose of the study. Descriptively, the data collected from the results of interviews with the teacher regarding his textbook for teaching were analyzed by interactive models. The results showed that the mathematical vocabulary was not yet the basis of school mathematics learning, because the textbooks he used lacked the mathematical vocabulary and were directly used for teaching.